Measurement of the forward-backward charge asymmetry in top-quark pair production - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2008)
We present the first measurement of the integrated forward-backward charge asymmetry in top-quark top-antiquark pair (tt) production in proton-antiproton (pp) collisions in the lepton+jets final state. Using a b-jet tagging algorithm and kinematic reconstruction assuming tt+X production and decay, a sample of 0.9 fb-1 of data, collected by the D0 experiment at the Fermilab Tevatron Collider, is used to measure the asymmetry for different jet multiplicities. The result is also used to set upper limits on tt+X production via a Z resonance. © 2008 The American Physical Society.